Climate and land‐use change will lead to a faunal "savannization" on tropical rainforests. (23rd October 2020) - Sales, Lilian P.; Galetti, Mauro; Pires, Mathias M.
Abstract: Humans have fragmented, reduced or altered the biodiversity in tropical forests around the world. Climate and land‐use change act synergistically, increasing drought and fire frequencies, converting several tropical rainforests into derived savannas, a phenomenon known as "savannization." Yet, we lack a full understanding of the faunal changes in response to the transformation of plant communities. We argue that the composition of vertebrate assemblages in ecotone regions of forest–savanna transitions from South America will be increasingly replaced by open savanna species, a phenomenon we name "faunal savannization." We combined projections from ecological niche models, habitat filter masks and dispersal simulations to forecast the distribution of 349 species of forest‐ and savanna‐dwelling mammal species across South America. We found that the distribution of savanna species is likely to increase by 11%–30% and spread over lowland Amazon and Atlantic forests. Conversely, forest‐specialists are expected to lose nearly 50% of their suitable ranges and to move toward core forest zones, which may thus receive an influx of more than 60 species on the move. Our findings indicate that South American ecotonal faunas might experience high rates of occupancy turnover, in a process parallel to that already experienced by plants. Climate‐driven migrations of fauna in human‐dominated landscapes will likely interact with fire‐induced changes in plant communities to reshape the biodiversity in tropical rainforests worldwide. Abstract : Anthropogenic stressors acting at local (e.g., fire and deforestation) and global scales (climate change) create warmer, drier, and open‐canopy habitats. Unsuitable for forest‐specialist fauna, these novel habitats allow the spread of species that are typical from open savannas. We argue that the composition of vertebrate assemblages in ecotone regions of forest‐savanna transitions from South America will be increasingly replaced by open savanna species, a phenomenon we name "faunal savannization." Climate‐driven migrations of fauna in human‐dominated landscapes will, therefore, interact with fire‐induced changes in plant communities to reshape the biodiversity in tropical rainforests.